Investigating undergraduate students' transitions within one institution of higher education - Karousou, Regina (2010)
The thesis explores the potentially problematic nature of transitions and the implications for the way students engage with (and disengage from) the process of learning. Although studies in the field of student experience, learning approaches and transitions have examined the relation between learning and contextual factors, there has not been an in-depth examination of the ways students cope with the changes at personal and academic level they are confronted with at university. This study draws initially upon the theories of Lave & Wenger to develop a theoretical model for conceptualising students' experiences of learning at university. The study is therefore able to provide additional insights into the way individual identity; institutional communities and the interaction between the personal and the social elements can play a role in students' experiences of their transitions to and in university. This is developed with a very specific focus on transitions from first to second year study at university.